2006
DOI: 10.4049/jimmunol.177.1.306
|View full text |Cite
|
Sign up to set email alerts
|

IL-2 In Vivo Activities and Antitumor Efficacy Enhanced by an Anti-IL-2 mAb

Abstract: IL-2 is a potent immunostimulant and has been tested for clinical use, including in immunotherapy for cancers and HIV infection. Here we show that a widely used neutralizing anti-murine IL-2 mAb (S4B6) exhibits unexpected activities that enhance the treatment effects of IL-2 in vivo. Coinjection of the anti-IL-2 mAb with a plasmid carrying murine IL-2 cDNA significantly increased the serum IL-2 levels and induced a substantial increase in the division of CD8+ T and NK1.1high cells in vivo. Injection of the mAb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
70
0

Year Published

2008
2008
2011
2011

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 65 publications
(81 citation statements)
references
References 45 publications
11
70
0
Order By: Relevance
“…This enhancing effect of nonlytic Fc fusion to IL-7 may be explained by the following reasons. First, it was reported that IL-2/anti-IL-2 mAb complexes enhance T-cell proliferation by increasing the in vivo half-life of cytokines [24][25][26]. As expected, the in vivo level of rIL-7 protein declined to undetectable levels (o200 pg/mL) 48 h after injection (t 1/2 5 2.5 h) (Supporting Information Fig.…”
Section: Discussionsupporting
confidence: 53%
“…This enhancing effect of nonlytic Fc fusion to IL-7 may be explained by the following reasons. First, it was reported that IL-2/anti-IL-2 mAb complexes enhance T-cell proliferation by increasing the in vivo half-life of cytokines [24][25][26]. As expected, the in vivo level of rIL-7 protein declined to undetectable levels (o200 pg/mL) 48 h after injection (t 1/2 5 2.5 h) (Supporting Information Fig.…”
Section: Discussionsupporting
confidence: 53%
“…19,21,24,25 Immunocomplexes of IL-3, IL-4, IL-6 and IL-7 with respective mAbs have been successfully used in various models of antitumor responses, autoimmune disease, graft tolerance or viral infections. [24][25][26] In our study, we employed IL-2/S4B6 immunocomplexes and showed that although they have considerable antitumor activity when injected soon after tumor cell inoculation, they are almost ineffective when used for treatment of advanced tumors. However, when the mice bearing advanced tumors were first treated with polymeric conjugate, which impairs the immune system to lower extent than free doxorubicin and possesses at least comparable antitumor activity, IL-2/S4B6 immunocomplexes significantly improved the therapeutic outcome.…”
Section: Discussionmentioning
confidence: 91%
“…23 Although powerful stimulatory activity of IL-2 immunocomplexes was described previously 19 and IL-2 immunocomplexes are an emerging class of immunostimulants, 32 there are a limited number of reports investigating their potential in cancer immunotherapy. Kamimura et al 26 showed that coinjection of S4B6 mAb with a plasmid carrying murine il2 cDNA is capable to reduce the number of B16 melanoma lung metastasis to half that seen with injection of the plasmid alone. Other studies have described the antitumor activity of IL-2 immunocomplexes, which was especially prominent when coadministrated with poly I:C. 33 However, the tumor elimination described in our work was achieved by adoptive transfer of tumor-specific T cells followed by treatment with IL-2 immunocomplexes and was thus a rather artificial model of tumor treatment.…”
Section: Discussionmentioning
confidence: 99%
“…However, controversy about the dual role of IL-2 in enhancing proliferation of both CD8 effector cells and CD4 regulatory T cells (Tregs), both of which express high levels of CD25, has raised some questions about the use of this cytokine in vivo (9). Recent studies have shown that the effect of the cytokine can be amplified and directed more specifically to CD8 cells rather than Tregs if IL-2 is complexed with the mAB S4B6 (10,11). IL-15 bound to IL-15R␣, its natural ''presenting'' receptors, has been shown to have a similar effect on CD8 memory cells and tumor-infiltrated cells (12)(13)(14), and IL-7/anti-IL-7 mAb complexes have been found to induce expansion of both naïve and memory CD8 and CD4 T cells (15).…”
Section: Cd8 T Cells ͉ Cytokine Complexes ͉ Interleukin-2 ͉ Tlr ͉ Tummentioning
confidence: 99%
“…The various ␥c-cytokine complexes influence proliferation of different immune cell types. IL-2c and IL-15c preferentially affect memory CD8 T cells, natural killer cells, and CD11cϩ cells (11,12,16), whereas IL-7c demonstrates its greatest effect on the numbers of B cells and macrophages [supporting information (SI) Fig. S1].…”
Section: Il-2 and Il-15 Complexes Enhance Activation Of Naïve Cd8 T Cmentioning
confidence: 99%